Enhancing Student Literacy and Engagement through the Development of STEM-Focused Educational Materials - Anggraini, Ade Eka; Suciptaningsih, Oktaviani Adhi; Dewi, Radeni Sukma Indra; Mirnawati, Lilik Binti; Zamroni, Moh. Rozy; Rahmayanti, Rissky; Mat, Hamidah (Jurnal Pendidikan Humaniora, 2023)
In the evolving landscape of education, the fusion of STEM (Science, Technology, Engineering, and Mathematics) disciplines with literacy education emerges as a pivotal strategy for fostering comprehensive learning. Despite its significance, elementary schools face obstacles in seamlessly incorporating STEM principles into their curricula, highlighting a gap in effective STEM-based educational practices. This research endeavors to pinpoint the hurdles impeding STEM integration and to devise strategic interventions aimed at bolstering STEM-centric learning, with a special emphasis on enhancing student literacy. Through detailed observations and dynamic discussions with key school stakeholders—including Principals and faculty members—the study identified foundational challenges such as a limited grasp of STEM concepts among teachers, a scarcity of relevant instructional materials, an absence of innovative strategies for teaching literacy and technology, and a general unfamiliarity with STEM-focused pedagogy. Responding to these challenges, the study orchestrated a series of targeted interventions. These included Focus Group Discussions (FGD) to foster a collaborative learning environment, literacy-centric training workshops to empower educators, an expansion of school library resources to include STEM-related materials, and support in crafting student textbooks that are oriented towards STEM learning. The post-intervention phase unveiled significant progress: educators exhibited a more profound understanding of how to develop STEM-focused learning materials and acknowledged the critical role of literacy and numeracy in student education. The strategic interventions not only mitigated the initial barriers but also equipped educators in elementary schools with the essential tools and knowledge to guide their students through an integrated learning journey in literacy and numeracy, underpinned by the core tenets of STEM education. This transformation underscores the effectiveness of the tailored approaches in enhancing the educational framework to support student success in a STEM-driven future.